(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Plants serve as a very rich source of bioactive molecules, which are used to treat various acute and chronic diseases in Ayurveda. Medicinal plant materials are formulated into various types of Ayurvedic medicine either by ancient or modern methods where standardization plays a pivotal role for authentication. Standardization confirms the identity, quality and purity of drugs. WHO has set up various parameters to evaluate the crude drugs and their finished products. Now a day’s application of several modern analytical techniques has become inevitable for evaluating quality, safety and efficacy of the polyherbal Ayurvedic formulations. Out of several formulations available in Ayurveda, Anjana is considered as unique in Shalakya Tantra due to its various forms (which are prepared by different ways). This article is about the formation of Nagaradi Anjana as ointment which can be taken as a form of Raskriyanjana. Most of the ingredients of Nagaradi ointment are Chakshushya i.e., good for eyes and also have Kaphashamak properties. That is why they are useful in ocular diseased conditions which have dominance of Kapha dosha like Kaphaja Abhishyanda. Keeping all these points in view, the present study has been undertaken with the aim to make the Ayurvedic formulation in the form of Raskriya Anjana or ointment, from the herbal drugs, mentioned in Astanga Sangrah, an Ayurvedic classical text and to develop the physiochemical profile of it. The eye ointment was prepared by using vaseline as base which is mixed with powdered Ghana Satva of the herbal drugs.